SARS-CoV-2 Testing of the Maxillary Sinus Immediately after COVID-19 Recovery - Takahiro Maeba, MD, PhD; Haruka Watanabe, MD; Naoki Wakuta, MD, PhD (Plastic and Reconstructive Surgery, Global Open, 2023)
Summary:. We report the case of a 19-year-old woman with left orbital floor fracture after a motorcycle accident. She presented with headache and diplopia; computed tomography showed herniation of the inferior rectus muscle into the maxillary sinus with orbital floor fracture. She was admitted for observation of her concussion and tested positive for coronavirus disease 2019 (COVID-19) half a day after admission. Her COVID-19 symptoms were mild; the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) antigen quantification test was below the standard value on the 10th day of hospitalization, and her isolation was lifted. She had diplopia with vertical eye motion disorder and underwent reconstruction of her orbital floor fracture on the 11th day. Although the orbital floor was connected to the maxillary sinus due to the orbital floor fracture, the presence and the viral load of SARS-CoV-2 in the maxillary sinus were unknown. The surgeons performed the operation while wearing N95 masks. A SARS-CoV-2 antigen quantification test and PCR test were performed on a sample from the maxillary sinus mucosa obtained through the orbital floor fracture before reconstruction of orbital floor with a titanium mesh implant; both were negative. To our knowledge, this is the first report of SARS-CoV-2 testing from the maxillary sinus immediately after COVID-19 recovery. We believe that the risk of SARS-CoV-2 infection from the maxillary sinus is small if the antigen test from the nasopharynx is negative.